Barbados : Request for an Extended Arrangement Under the Extended Fund Facility-Press Release; Staff Report; Staff Supplement; and Statement by the Executive Director for Barbados. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses Barbados' Request for an Extended Arrangement Under the Extended Fund Facility (EFF). The authorities have requested a 4-year EFF arrangement that would be appropriate given the structural nature of fiscal imbalances and the extensive need for structural reforms to support fiscal consolidation and growth promotion. The prior action on launching the domestic part of the debt restructuring would be supplemented by a medium-term structural reform agenda. In view of Barbados' balance-of-payments needs and the comprehensive package of measures proposed by the authorities, the IMF staff supports the authorities' request for a four-year extended arrangement under the EFF in the amount of 220 percent of quota.